Analisis Yuridis Penerapan Peraturan Pemerintah Nomor 16 Tahun 2021 tentang Bangunan Gedung di Provinsi DKI Jakarta - Sudrajat; Sinaga, Parbuntian; Setyowati, Retno Kus (Pusat Riset dan Inovasi Nasional, 2025)
This research discusses the Juridical Analysis of the Application of Government Regulation Number 16 of 2021 concerning Building in DKI Jakarta Province. The focus of the research is directed at the effectiveness of local policies in adjusting national regulations to the diverse urban dynamics of Jakarta, especially related to the Building Approval mechanism (PBG), supervision system, and enforcement of administrative sanctions. Using a normative juridical approach and analyzing local regulations such as Government Regulation No. 16 of 2021 on the Implementation Regulation of Law No. 28 of 2002 on Building, this research identifies implementative obstacles, such as weak supervision, limited human resources, and low public legal awareness. The findings show that adaptation efforts have not been fully optimized, so policy adjustments, institutional strengthening, and cross-sector collaboration are needed. This research confirms the importance of digitalization, public participation, and consistency of law enforcement in creating orderly and sustainable building development in Jakarta.